2020
DOI: 10.1002/pros.23949
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and therapeutic value of pelvic lymph node dissection in the fossa of Marcille in patients with clinically localized high‐risk prostate cancer: Histopathological and molecular analyses

Abstract: Background: The optimal extent of lymph node dissection in radical prostatectomy has not been determined. Lymph nodes in the fossa of Marcille, which is an important pelvic lymphatic pathway and candidate for additional dissection, have not been evaluated at the molecular level. Here, we assessed by molecular analysis the presence of occult positive lymph nodes in the fossa of Marcille in patients with clinically localized high-risk prostate cancer.Methods: Fifty-two patients with clinically localized high-ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…[21][22][23][24] It has been reported that the isolated metastasis to this area is less likely, and that metastasis is frequently confirmed when multiple lymph node metastasis is found elsewhere. 22 On the other hand, many urologists dissect the fossa of Marcille for prostate and bladder cancer because it facilitates en bloc dissection of the obturator lymph nodes around the obturator nerve. In bladder cancer, the treatment significance of lymph node dissection extending to the para-aortic lymph nodes has also been discussed, but at present, opinions generally recommend dissection distal to the common iliac bifurcation.…”
Section: Plnd In Urologic Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…[21][22][23][24] It has been reported that the isolated metastasis to this area is less likely, and that metastasis is frequently confirmed when multiple lymph node metastasis is found elsewhere. 22 On the other hand, many urologists dissect the fossa of Marcille for prostate and bladder cancer because it facilitates en bloc dissection of the obturator lymph nodes around the obturator nerve. In bladder cancer, the treatment significance of lymph node dissection extending to the para-aortic lymph nodes has also been discussed, but at present, opinions generally recommend dissection distal to the common iliac bifurcation.…”
Section: Plnd In Urologic Surgerymentioning
confidence: 99%
“…In addition to the internal iliac, obturator, and external iliac regions, extended PLND including the common iliac and sacral regions is recommended for bladder cancer 11,20,21 . The area called “the fossa of Marcille,” located lateral to the common iliac vessels, medial to the psoas muscle, anterior to the sciatic nerve, and cephalic to the obturator lymph nodes, is considered an important lymphatic route from the prostate and bladder and has long been considered by urologists to be an area that needs to be dissected 21–24 . It has been reported that the isolated metastasis to this area is less likely, and that metastasis is frequently confirmed when multiple lymph node metastasis is found elsewhere 22 .…”
Section: Review Of the Evidences For Plnd In Each Departmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Marcille's triangle or fossa has been given special attention in the creation of adequate anatomical templates for lymph node dissection. Lymph nodes located in this region are covered by the iliac vessels and therefore less obvious, but are considered relevant for achieving optimal lymph node clearance [31][32][33].…”
Section: Surgerymentioning
confidence: 99%
“…A rather neglected lymph node region extends behind the proximal iliac vessels and corresponds to the triangle or fossa of Marcille, which is explored surgically by some surgeons during extended or salvage lymphonodectomy [31][32][33]. Marcille's triangle is limited by the anterolateral aspect of the fifth lumbar vertebra, the medial border of the psoas muscle, and the ala of the sacrum (see Figure 6B).…”
Section: Anatomymentioning
confidence: 99%